Kompetensi Peradilan Militer Bagi Prajurit TNI Dalam Tindak Pidana Umum - Arief Fahmi Lubis (Islamic Sharia Coll, 2021)
Military justice is the executor of judicial power within the armed forces to uphold law and justice by taking into account the interests of administering national defense. Article 7 of Law Number 31 of 1997 states that organizational and procedural, administrative and financial guidance for court and judiciary bodies is carried out by the Commander in Chief. This guidance must not reduce the freedom of judges in examining and deciding cases. The aim of this research is to show that Article 9 number 1 which is linked to Articles 1 and 2 of the KUHPM above, can be concluded that the absolute competence of military justice which is based on the subject of criminal acts has placed soldiers as a very special group because almost all violations and crimes those committed by soldiers will be brought under the realm of military justice. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description at the time of the research. The results of this research show that the determination of absolute competency based on the severity of the loss can be said to be in line with what is stated in Article 3 paragraph (4) letter a TAP MRP Number VII of 2000 concerning the Role of the Indonesian National Army and the Role of the National Police of the Republic of Indonesia which states